Secondary alcohol dehydrogenase catalyzes the reduction of exogenous acetone to 2-propanol in Trichomonas vaginalis - Sutak, Robert; Hrdy, Ivan; Dolezal, Pavel; Cabala, Radomir; Sedinová, Miroslava; Lewin, Joern; Harant, Karel; Müller, Miklos; Tachezy, Jan (The FEBS journal, 2012)
Secondary alcohols such as 2-propanol are readily produced by various anaerobic bacteria that possess secondary alcohol dehydrogenase (S-ADH), although production of 2-propanol is rare in eukaryotes. Specific bacterial-type S-ADH has been identified in a few unicellular eukaryotes, but its function is not known and the production of secondary alcohols has not been studied. We purified and characterized S-ADH from the human pathogen Trichomonas vaginalis. The kinetic properties and thermostability of T. vaginalis S-ADH were comparable with bacterial orthologues. The substantial activity of S-ADH in the parasite's cytosol was surprising, because only low amounts of ethanol and trace amounts of secondary alcohols were detected as metabolic end products. However, S-ADH provided the parasite with a high capacity to scavenge and reduce external acetone to 2-propanol. To maintain redox balance, the demand for reducing power to metabolize external acetone was compensated for by decreased cytosolic reduction of pyruvate to lactate and by hydrogenosomal metabolism of pyruvate. We speculate that hydrogen might be utilized to maintain cytosolic reducing power. The high activity of Tv-S-ADH together with the ability of T. vaginalis to modulate the metabolic fluxes indicate efficacious metabolic responsiveness that could be advantageous for rapid adaptation of the parasite to changes in the host environment.
Keywords: Trichomonas vaginalis; biologické modely; Base Sequence; Catalysis; protozoální proteiny; Female; Kinetics; Phylogeography; 2-Propanol; železo; katalýza; ženské pohlaví; Acetone; Alcohol Oxidoreductases; Protozoan Proteins; energetický metabolismus; lidé; Models, Biological; Host-Parasite Interactions; 2-propanol; interakce hostitele a parazita; Energy Metabolism; DNA primery; alkoholoxidoreduktasy; oxidace-redukce; Male; Oxidation-Reduction; Iron; fylogeografie; sekvence nukleotidů; aceton; DNA Primers; mužské pohlaví; Enzyme Stability; kinetika; stabilita enzymů; Humans